Hope, Agency, and the Lived Experience of Violence: A Qualitative Systematic Review of Children's Perspectives on Domestic Violence and Abuse. (July 2021) - Arai, Lisa; Shaw, Ali; Feder, Gene; Howarth, Emma; MacMillan, Harriet; Moore, Theresa H. M.; Stanley, Nicky; Gregory, Alison
There is a large body of research on the impact of domestic violence and abuse (DVA) on children, mostly reporting survey data and focusing largely on psychological outcomes. Qualitative research on the views of children has the potential to enable a child-centered understanding of their experience of DVA, so their needs can be better met by professionals. This systematic review reports general findings from the ViOlence: Impact on Children Evidence Synthesis (VOICES) project that synthesized published qualitative research on the experiences of DVA from the perspective of children and young people. A thematic synthesis of 33 reports identified six themes: lived experience of DVA, children's agency and coping, turning points and transitions, managing relationships postseparation, impact of DVA on children, and children's expressions of hope for the future . We conclude that professionals working with children affected by DVA should be mindful of the diversity in children's experiences and listen carefully to children's own accounts.